Principle-right to equality and disability pension in the Private Pension System: disability as a valid reason for exclusion? - Espino Layza, María Alejandra (2019)
From the conception of the social model of disability and the entry into force of international instruments that seek to promote the rights of people with disabilities on equal opportunities.This paradigm shift has impacted all the institutions of law, including those concerning social security. Therefore, through this article we seek to highlight a problem that affects all people with disabilities at the time of seeking access to disability pension. As we will see, in our legal system, disability is understood as an assumption of exclusion from this pension, even when people with disabilities meet the minimum number of contributions to the private pension system. Thus, here we will seek to unravel the problems posed and propose some guidelines for a solution.